2020
DOI: 10.1177/0333102420974351
|View full text |Cite
|
Sign up to set email alerts
|

Update on headache and brain tumors

Abstract: Headache is one of the leading symptoms often associated with brain tumours. Secondary headaches attributed to intracranial neoplasias have been included in subchapter 7.4 of the third edition of the International Classification of Headache Disorders (ICHD-3). According to ICHD-3, the headache may be attributed to a brain tumour if it has developed in close temporal relation with the development of the neoplasia, has significantly worsened in parallel with the worsening of the tumour, and/or has significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 42 publications
1
26
0
2
Order By: Relevance
“…This is probably due to a selection bias, since patients referred from these specialists usually have a serious condition (systemic or specifically involving the CNS), which increases the a priori probability of having structural abnormalities. Of note, it has been suggested that the addition of oncologic history as a specific sub-criterion may improve sensitivity of classification of tumor headache, considering the a priori increased risk of metastasis to the brain [ 40 , 41 ]. In fact, multivariate analyses showed that it was the presence of previously diagnosed conditions rather than the medical specialty of the ordering physician that was associated with presence of structural anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to a selection bias, since patients referred from these specialists usually have a serious condition (systemic or specifically involving the CNS), which increases the a priori probability of having structural abnormalities. Of note, it has been suggested that the addition of oncologic history as a specific sub-criterion may improve sensitivity of classification of tumor headache, considering the a priori increased risk of metastasis to the brain [ 40 , 41 ]. In fact, multivariate analyses showed that it was the presence of previously diagnosed conditions rather than the medical specialty of the ordering physician that was associated with presence of structural anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the low number of tumors in our cohort precluded multivariate regression models from being applied, the overall findings are in agreement with previous studies which found that the combination of headache with specific associated symptoms increases the positive predictive value of neuroimaging exams [ 42 ]. Of note, although tumor headache was traditionally thought to display some specific clinical characteristics (e.g., worsening in the morning, being aggravated by Valsalva-like maneuvers and accompanied by nausea and/or vomiting, with a tendency to decrease later in the day) [ 43 ], the studies performed after the advent of modern neurodiagnostic techniques have pointed out that the “classic” brain tumor headache is uncommon, particularly at the time of clinical presentation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 previously diagnosed with brain tumor, repeat imaging should be considered if headache features change, if new neurologic symptoms or focal signs on exam develop, or if seizure, cognitive change, and/or signs of intracranial hypertension are identified. 13 Though the chance of finding a brain tumor on imaging in a headache patient with no history of malignancy is low, 27,29 MRI or computed tomography (CT) of the brain can help identify space-occupying cerebral lesions. MRI is superior to CT both in terms of imaging resolution and visualization of the brain's posterior fossa, whereas CT is more widely available and can be helpful in evaluating for a hemorrhagic component of tumor and/or associated cerebral edema.…”
Section: Red Flagmentioning
confidence: 99%
“…При отсутствии явных признаков иммунодефицита необходимо отметить наличие очагов хронической инфекции и хирургических манипуляций в анамнезе (синуситы, отиты, инфекционный эндокардит, недавнее лечение зубов, нейрохирургическое вмешательство), так как возможно распространение инфекции с формированием абсцесса головного мозга, причем присутствие триады симптомов в виде ГБ, лихорадки и неврологического дефицита отмечается всего у 20% пациентов [29]. При объемном образовании головного мозга в 60% случаев пациента беспокоит цефалгия, которая часто отмечается в ночное и утреннее время, сопровождается потерей массы тела, тошнотой, рвотой и другой очаговой неврологической симптоматикой [30,31].…”
Section: особенности дифференциальной диагностики гбunclassified